Shear performance of FRP Reinforced Deep Beams Made of Ultra High Performance Concrete (UHPC) - Salman, Omar (2023)
A Master of Science thesis in Civil Engineering by Omar Salman entitled, “Shear performance of FRP Reinforced Deep Beams Made of Ultra High Performance Concrete (UHPC)”, submitted in December 2023. Thesis advisor is Dr. Farid Abed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).